1997
DOI: 10.1038/sj.sc.3100341
|View full text |Cite
|
Sign up to set email alerts
|

The functional independence measure in spinal cord injured patients: comparison of questioning with observational rating

Abstract: Functional independence measure (FIM) is becoming widely used for all aspects of disabling diseases including spinal cord injury (SCI). It is recommended that it is rated by trained clinicians familiar with the patients. We aimed to compare the ratings of those patients who were questioned with those who were observed in a simulated environment.Fifty patients with SCI were included in the study. They were all FIM rated by the same clinician, ®rst by questioning and then by observation. Although observational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 4 publications
0
13
0
4
Order By: Relevance
“…Studies showed that there was satisfactory agreement between the clinician observational scores and subjects' self-reports on FIM motor and cognitive scores. 7,8 The telephone version of FIM called FONE FIM was also validated locally with satisfactory psychometric properties. 9 The functional status was measured by the Functional Independence Measure (FIM).…”
Section: Methodsmentioning
confidence: 99%
“…Studies showed that there was satisfactory agreement between the clinician observational scores and subjects' self-reports on FIM motor and cognitive scores. 7,8 The telephone version of FIM called FONE FIM was also validated locally with satisfactory psychometric properties. 9 The functional status was measured by the Functional Independence Measure (FIM).…”
Section: Methodsmentioning
confidence: 99%
“…However, the observational rating is more time consuming and requires a proper environment and is more laborious. 20 In the present study, the questioning ratings were used, which could underestimate the ability of individuals to perform the motor FIM tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the BI and MBI, the original FIM has been assessed in a number of studies with SCI patients 48,[21][22][23] , as have the more recent adapted versions 29,27,28,49 of the FIM. The SIP68 has also been evaluated with SCI patients in two studies with relatively large sample sizes.…”
Section: Instrumentsmentioning
confidence: 99%